Unclassified unilateral persistent sciatic artery in a patient with chronic intermittent claudication - Kristina Duan, BS (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
Patients with persistent sciatic artery are at high risk for development of limb ischemia, aneurysm formation, and embolism. In this report, we identify a nonclassified left leg persistent sciatic artery in a patient with chronic limb ischemia. Vascular reconstruction was carried out by common iliac-deep femoral artery bypass to restore adequate arterial flow. Our approach to placement of the distal anastomosis on the deep femoral artery instead of on the popliteal artery, which is used in routine practice, may potentially increase treatment efficacy and decrease surgical complications. At 2-year follow-up, the patient remained asymptomatic and in good health. Keywords: Persistent sciatic artery (PSA), Bypass, Patency